Steady State Vortex Structure of Lid Driven Flow Inside Shallow Semi Ellipse Cavity - M. S., Idris; M.Irwan, M. A.; N. M. M., Ammar (Faculty Mechanical Engineering, UMP, 2012)

(untitled)
In this paper, the lid driven cavity flow inside semi-ellipse shallow cavity was simulated using stream function vorticity approach emphasizing non-uniform grid method. Three aspect ratio of 1/4, 1/3 and 3/8 were simulated using laminar flow conditions (range of Reynolds numbers of 100-2000). Primary and secondary vortexes were extensively monitored through centre vortex location, streamlines pattern and peak stream function value. Secondary vortex developed at Re 1500 for the aspect ratio of 1/4 while the secondary vortex formed at earlier Reynolds number of 1000 for the aspect ratio of 1/3 and 3/8. The size of secondary vortex increases as Reynolds number increases. The similar trends can be observed the differences between primary vortex separation angle and reattachment angle. For the entire streamline pattern, many primary vortex centre locations situated at the right side of the cavity.